Burglaries and entry controls in gated communities. (November 2021) - Wang, Zengli; Liu, Lin; Haberman, Cory; Lan, Minxuan; Yang, Bo; Zhou, Hanlin
This article examines whether different levels of entry controls impact burglary rates in gated communities. It differs from the previous studies that only distinguish gated communities from non-gated communities but ignore important variation in different levels of entry controls. A sample of 698 gated communities in a large Chinese city are selected for this study. A negative binomial regression model estimates the relationships between entry control levels and burglary rates in gated communities. The test of these relationships accounts for the control of other important explanatory variables, including management fee, building height, building age, housing price, house for sale, rental house and floating population. Results indicate that higher entry control levels are associated with significantly lower burglary rates in gated communities. This is the first study that reveals a quantitative relationship between burglary and entry control level in gated communities at the city-wide scale.